IMPROVING THE EFFICIENCY OF OPERATING THE CONE LAYING AND COLLECTING MACHINE (C2L) USING TRIZ METHOD - Reza, M.; Salim, M.A.; Masripan, N.A.; Yusof, N.M.; Purnomo, M.R.A. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
This article presents the process of redesigning the guidepost of Cone Laying and Collecting (C2L) machine, a semi-automated system that collects and lay cones. The guidepost in the first prototype, Phase 1 C2L, consists of multiple parts, which complicates the assembly and disassembly process, reducing overall operational efficiency. By redesigning the guidepost, this study aims to reduce the time and process steps when assembling and disassembling the guidepost, thereby improving its ease of use. By utilizing TRIZ’s Trend of Flow Enhancement, the guidepost was redesigned as a singular foldable unit, eliminating the need to use screw to attach different parts together. The experiments showed that the new guidepost design reduced the time to assemble and disassemble by 92 % and reduced the process steps by half. This research not only achieved its intended objective but also highlights other potential advantages related to design simplifications. However, before it can be used under real-world operational settings, Phase 2 C2L still needs to be tested under actual working conditions so that any underlying issues can be identified and addressed.